3(-1-v)=-9

Simple and best practice solution for 3(-1-v)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-1-v)=-9 equation:



3(-1-v)=-9
We move all terms to the left:
3(-1-v)-(-9)=0
We add all the numbers together, and all the variables
3(-1v-1)-(-9)=0
We add all the numbers together, and all the variables
3(-1v-1)+9=0
We multiply parentheses
-3v-3+9=0
We add all the numbers together, and all the variables
-3v+6=0
We move all terms containing v to the left, all other terms to the right
-3v=-6
v=-6/-3
v=+2

See similar equations:

| 9=k-2+7 | | -6=x/4+2 | | 1674=27(p+30) | | 9u-18=54 | | 2c+12=26 | | 6(2x-1)=3(2x+1) | | 1+17x=-23+19x | | -53=7+4m | | 1674=27(x+30) | | 1=p÷4-4 | | 19.8-1.7k=-8k+4.9k-6.1 | | 15p-14p=6 | | Y=300x+30 | | 4(2c+8)=5(c+40 | | 16n-10n=12 | | -7p=-17-8p | | 6v-3v=63 | | -10+10p=19-2+13p | | 290x=50+20 | | 90+(4w+4)=180 | | 4(3x+1)=5(3x-1) | | 15u+-16u=12 | | (1+2x)=1.024 | | 0.625x=30 | | 4(13/5)+y=8 | | 8g+1=-3+7g | | H=100t-10t2 | | -10-6k+2-3k=-8k+1k | | (3/20)=(y/1 | | b=13b-62 | | 4x+124=3 | | 14r-15=11r |

Equations solver categories